New insight in the cross-talk between microglia and schizophrenia: From the perspective of neurodevelopment - Li, Jingjing; Wang, Yu; Yuan, Xiuxia; Kang, Yulin; Song, Xueqin (Frontiers in Psychiatry, 2023)
Characterized by psychotic symptoms, negative symptoms and cognitive deficits, schizophrenia had a catastrophic effect on patients and their families. Multifaceted reliable evidence indicated that schizophrenia is a neurodevelopmental disorder. Microglia, the immune cells in central nervous system, related to many neurodevelopmental diseases. Microglia could affect neuronal survival, neuronal death and synaptic plasticity during neurodevelopment. Therefore, a hypothesis proposes that the abnormal function of microglia leads to the occurrence of schizophrenia. Nowadays, accumulating experiments between microglia and schizophrenia could afford unparalleled probability to assess this hypothesis. Herein, this review summarizes the latest supporting evidence in order to reveal the mystery of microglia in schizophrenia.